Determination of heterogeneities in the hydraulic properties of a phreatic aquifer from tidal level fluctuations: a case in Argentina - Carol, Eleonora Silvina (2009)
A well-known analytical solution of Jacob (1950) for groundwater flow due to tidal-wave propagation, together with field measurements along a complete tidal cycle and geological data, were used to evaluate the heterogeneities in the hydraulic properties of a phreatic aquifer located next to the River Ajo in the coastal plain environment of the southern sector of the Samborombon Bay wetland, Argentina. From the analysis of water-table fluctuations in a set of monitoring wells located along a riverbank-normal transect, it was possible to quantify the piecewise spatial variations of the hydraulic diffusivity of the phreatic aquifer. The results show the strong lateral variations of the sedimentary environment due to the influence of the different transport and deposition agents that characterize the coastal plain. The known thickness of the phreatic aquifer and the estimated range of the specific yield allowed the hydraulic conductivity to be identified as the most influential factor. [Jacob CE (1950) Flow of ground water. In: Rouse H (ed) Engineering Hydraulics. Wiley, New York]